Building a capital market for start-up enterprises contributing successfully to industrialization and modernization - Nguyen Thanh Huyen (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Startups in the field of STI (science, technology, and innovation) are becoming increasingly important to economies, because its research and application of technology can lead to output increasing and contribute a solid economic development. Government funding always plays an important and decisive role in helping and creating a premise and motivation for startup’s technology research and application. However, due to increasingly high costs, state budget funding shortage, and regulations limiting subsidies... it is necessary to have capital mobilization methods for effective startup STI funding that can create a driving force for sustainable development in the future. The capital market is a part of the financial market that plays an intermediary role in facilitating and regulating the flow of money from places with excess capital to places in need of capital. Normally, to mobilize capital through this capital market, businesses often have to meet legal criteria such as capital criteria, business performance results, and corporate governance... These legal criteria are big obstacles for startups. Therefore, researching and building a specific Startup’s Stock Exchange floor will create opportunities for startups to access the capital market/stock market to mobilize capital easily and at lower costs. Code: 23101001